AB0324 Physical Activity in Patients with Rheumatoid Arthritis. (10th June 2014) - El Kabbaj, S.; Allali, F.; Ben Slama, I.; Lakhdar, T.; Medrare, L.; Ngeuleu, A.; Rkain, H.; Hajjaj-Hassouni, N.
Abstract : Objectives: The purpose of this study was to identify physical activity behaviors of Moroccan patients with RA and her associations with RA demographic and disease related variables. Methods: A cross sectional study was conducted in 103 RA. Socio-demographic characteristics and Disease specific variables were documented. Disease activity was measured with Disease Activity Score 28 (DAS28), quality of life was assessed with rheumatoid arthritis impact disease (RAID), fatigue was evaluated by fatigue Visual Analogic scale and Health Assessment Questionnaire (HAQ) was completed by all patients. Physical activity was evaluated with the Arab version of the International Physical Activity Questionnaire (IPAQ) short version. Results: A total of 90 women and 13 men with RA participated in this study. Mean age of participants was 49.7±11.4.disease duration was a median of 8.16 years [3, 25-14, 16]. Total amount of physical activity was a median of 1873 (346-4053) MET-minute/week. However in 30.8% the physical activity was low. In univariate analysis lower physical activity (IPAQ) correlated with higher disease activity (OR=-3.9; CI95%>899–300; p<0, 001); poor functional capacity (OR=-4.5; CI95%>2146–845; p=<0.001); higher fatigue levels (OR=-2.3; CI95%>43.4–3.3; p=0, 02) and low quality of life (RAID) (OR=-2.8; CI95%>610–107p=0, 006). No relationship was found between PA, age, disease duration and BMI. After multivariate analysis HAQ (OR=-3.1; CI95%>991–85; p=0.002) and DAS28 (OR=-3.1;CI95%>2587–606) still strongly associated with PA. Conclusions: This study suggested that lower physical activity associated with high disease activity and poor functional capacity. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5826